2022
DOI: 10.3390/ani12091219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Plateau Environment on the Oxidation State of the Heart and Liver through AMPK/p38 MAPK/Nrf2-ARE Signaling Pathways in Tibetan and DLY Pigs

Abstract: This study evaluated the effect of a plateau environment on the heart and liver oxidation state of Tibetan pigs (TPs) and DLY pigs through analyzing AMPK, p38 MAPK, and Nrf2 signaling pathways. Twelve 120-day-old TPs and twelve 120-day-old DLY pigs were randomly divided into two groups in a plateau environment for three weeks. Exposed to a plateau environment, TPs exhibited a lower (p < 0.05) malondialdehyde level but higher (p < 0.05) glutathione, superoxide dismutase (SOD), glutathione peroxidase (GSH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…While we did not find any genes from 56 genomic regions showing significant genetic divergence (PBS > 1) that were differentially expressed in populations across the elevational gradient, there were shared biological pathways such as MAPK signaling and VEGFA-VEGFR2 signaling pathways, which are previously associated with adaptation to hypoxic environment [167][168][169] . We did not find evidence of genetic divergence or differential expression in some of the key genes such as EPAS1 gene (endothelial PAS domain protein 1, also known as HIF-2α) and EGLN1 (Egl Nine homolog 1), previously known to be associated with high-altitude adaptation.…”
Section: Discussioncontrasting
confidence: 65%
“…While we did not find any genes from 56 genomic regions showing significant genetic divergence (PBS > 1) that were differentially expressed in populations across the elevational gradient, there were shared biological pathways such as MAPK signaling and VEGFA-VEGFR2 signaling pathways, which are previously associated with adaptation to hypoxic environment [167][168][169] . We did not find evidence of genetic divergence or differential expression in some of the key genes such as EPAS1 gene (endothelial PAS domain protein 1, also known as HIF-2α) and EGLN1 (Egl Nine homolog 1), previously known to be associated with high-altitude adaptation.…”
Section: Discussioncontrasting
confidence: 65%
“…Another study investigated the effect of a plateau condition on oxidation in Tibetan pigs and Duroc × Landrace × Yorkshire (DLY) pigs, and found that Tibetan pigs exhibited higher SOD, GSH-Px, and T-AOC levels, but lower MDA levels in the liver and heart. Furthermore, the mRNA levels of SOD, GSH-Px , and Nrf 2 in the liver and heart of Tibetan pigs were higher than those in DLY pigs, and the authors suggest that Tibetan pigs held a stronger antioxidant activity through the AMPK/p38 MAPK/Nrf 2 -ARE signaling pathways ( 38 ). Wang and Li ( 18 ) found that the Zinc-HSP ( Hohenbuehelia serotina polysaccharides) complex (20 mg/mL) not only had superoxide anion radical scavenging ability, but also did not affect the biological activity of Hohenbuehelia serotina polysaccharides when combined with zinc.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters for thermal cycling were set in accordance with our published study [ 21 ]. Primers of Nrf2, SOD, GPX, CAT, Keap-1, TLR4, NF-κB, IL-1β, IL-6, IL-8, IL-10, TNF-α, mucin-2, zonula occludens (ZO) -1, ZO-2, occludin, claudin-1, claudin-1 and glyceraldehyde-3 phosphate dehydrogenase (GAPDH) were obtained from other reports [ 19 , 22 , 23 , 24 , 25 ] and are listed showed in Table S2 . All primers were commercially synthesized by Sangon Biotech Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%